Use of Expressions in Comparative Translations (In the Example of English Uzbek Languages) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information about the concept of phraseology, its development and tasks. The use of expressions in English and Uzbek languages, their characteristics, similarities and differences are also explained. In addition, the sources of great importance in Uzbek and English linguistics and their brief comments are also given. The benefits of comparing two unrelated languages to language learners and nations are also highlighted.